Factors. - Harper & Row, Publishers (White Plains, N.Y. : Center for Humanities, 1978)
Topics covered include prime and composite numbers, prime factors, divisibility tests, greatest common multiple, and least common denominator.
"The skills group."
Also issued with sound accompaniment on disc.
Keywords: Factors (Algebra); Numbers, Prime